Manhaj Muqtarah Li Ta’limi At-Ta’birat Al-Istilakhiyah Min Mu’jam At-Ta’bir Al-Istilakhi Fi Al ‘Arabiyah Al-Mu’ashirah - Danang Duwi Julian; kristiana (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
تهدف هذه الدراسة إلى لكشف منهج مقترح لتعليم التعبيرات الاصطلاحية من خلال معجم التعبير الاصطلاحي في العربية المعاصرة لمحمد محمد داود (حرف الميم) وذلك بذكر المعنى، بحيث التعبيرات الاصطلاحية لاتستمد معناها من الكلمات المكونة لها, وإنما من اتفاق الجماعة اللغوية, وهو ما يسمى بالاصطلاح أو تعارف. وإنها يساعد الطلاب على إثراء اللغة وترقيتها وبيان كيفية الاستفادة منها خاصة في تعليم اللغة العربية وإثراء لغة الطلاب بجامعة الراية. أثبتت الدراسة استيفادة التعبيرات الاصطلاحية في العربية المعاصرة من خلال معجم التعبير الاصطلاحي في العربية المعاصرة للدكتور محمد محمد داود (حرف الميم). وبلغ عدد التعبيرات الاصطلاحية حرف الميم 181 تعبيرا. ولقد أثبتت هذه الدراسة أن التعابير الاصطلاحية مع معانيها يمكن أن تصمم منهجا لتعليم التعبير الاصطلاحي للإندونيسيين لترقية المرحلة اللغوية والثقافية وحل بعض المشكلات اللغوية. This study is aimed to create a suitable curriculum for teaching Contemporary arabic idioms from “the Contemporary Arabic Idiom Dictionary (Letter M) Written by DR. Muhammad Muhammad Daud “ with meanings for each idiom, because Contemporary arabic idioms are hard to understand if they are understood word by word, but they have a specific meaning that is well know by all people. That is why they are called idioms , Contemporary arabic idioms help students increase their word bank and improve their languge. This research also explains how to use these idioms in increasing the word bank of the students of Ar-raayah in teaching arabic language and also improving the student’s language. This study uses Contemporary Arabic Idiom in “the Contemporary Arabic Idiom Dictionary (Letter M) Written by DR. Muhammad Muhammad Daud” while the number of idioms reaches 181 idioms. This study also formulates several affective ways in learning the idioms, by making a curriculum that is recommeded for the community in improving language and knowledge and providing solutions if they find any problems grammar.